2017
DOI: 10.1111/mec.14294
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell sequencing unveils the lifestyle and CRISPR‐based population history of Hydrotalea sp. in acid mine drainage

Abstract: Acid mine drainage (AMD) is characterized by an acid and metal-rich run-off that originates from mining systems. Despite having been studied for many decades, much remains unknown about the microbial community dynamics in AMD sites, especially during their early development, when the acidity is moderate. Here, we describe draft genome assemblies from single cells retrieved from an early-stage AMD sample. These cells belong to the genus Hydrotalea and are closely related to Hydrotalea flava. The phylogeny and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…genome from our metagenome data set. In doing so, we found our data to closely align with that of Medeiros et al (). Detailed information on the obtained Hydrotalea sp.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…genome from our metagenome data set. In doing so, we found our data to closely align with that of Medeiros et al (). Detailed information on the obtained Hydrotalea sp.…”
Section: Discussionsupporting
confidence: 90%
“…However, stronger correlations were found with Hydrotalea spp. Following this line of reasoning, the genus Hydrotalea was also previously reported to occur at a high relative abundance in the same AMD system (Medeiros et al, 2017). In addition, by using single-cell genomics, Medeiros et al…”
Section: Ecological Traits Potentially Involved With a Symbiotic LImentioning
confidence: 91%
See 1 more Smart Citation
“…Given that it is often challenging to culture the majority of uncharacterised microbial species, single cell sequencing enables culture-free sequencing of genomes for these organisms (Stepanauskas 2015;Woyke et al 2017). Several studies have demonstrated the use of single-cell sequencing directly on environmental samples to study uncharacterised microbial species in atypical microbial communities, including Oceanospirillales in oil spillcontaminated sea water (Mason et al 2012), Hydrotalea in highly acidic mine drainage (Medeiros et al 2017) and Poribacteria, endosymbionts in marine sponges (Siegl et al 2011). However, the application of single-cell sequencing is restricted to a microbial community where cells can be isolated relatively easily (Woyke et al 2017).…”
Section: Advancing Our Understanding Of Plant Rhizospheric Signallingmentioning
confidence: 99%
“…Many bio-techniques like deep sequencing, single cell sequencing, CRISPR, etc . 24 - 26 are developed as efficient tools for the deep investigation of the complex mechanisms of complex disease like CCA. The accumulation of big sequencing data and other clinical data provides the opportunity, but also the challenge, to build bioinformatics models for early diagnosis and personalized treatment, even prevention of cancers like CCA and others.…”
Section: Introductionmentioning
confidence: 99%